PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI 017 BAGAN LIMAU KECAMATAN UKUI KABUPATEN PELALAWAN - Sambi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The problem addressed in this research was the low mathematics learning outcomes of second-grade students at SD Negeri 017 Bagan Limau, Kecamatan Ukui. Of the 24 students, only 14 students (61.7%) had achieved the minimum mastery criterion (KKM). This study was conducted as classroom action research by applying the Quantum Teaching learning model and was implemented in two cycles. The subjects of the study were second-grade students of SD Negeri 017 Bagan Limau, Kecamatan Ukui. Data were collected through observation techniques, including teacher and student activity observation sheets, as well as mathematics achievement tests. The results showed an improvement in students’ mathematics learning outcomes. Teacher activity increased from 53.66% in the first meeting of Cycle I to 64.29% in the second meeting, then rose to 73.81% in the first meeting of Cycle II and reached 88.09% in the second meeting. Student activity also increased from 54.76% in the first meeting of Cycle I to 61.91% in the second meeting, then rose to 76.19% in the first meeting of Cycle II and reached 85.72% in the second meeting. In addition, students’ learning outcomes improved, as indicated by the increase in the average score from 70.7 in the baseline data to 83.3 in Cycle I and 92.7 in Cycle II. The number of students who achieved mastery learning also increased from 14 students (61.7%) in the baseline data to 18 students (76.4%) in Cycle I and 21 students (87.5%) in Cycle II. These results indicate that the application of the Quantum Teaching learning model can improve mathematics learning outcomes of second-grade students at SD Negeri 017 Bagan Limau.